How can technology assist occupational voice users? (2020)
Summary: The voice is an important tool for people who use it daily in their occupations. However, what technological options are available to such individuals to allow them to monitor or take care of their voices? Objective: The purpose of this study is to answer two research questions: (1) What technologies exist to monitor or take care of the voice in occupational voice users? (2) What is the technology readiness level (TRL) of the technologies used to monitor or take care of the voice in occupational voice users? Data sources: Embase, IEEE, Medline, Proquest, PubMed, Scopus, and Web of Science, Methods: A systematic literature review was conducted. Articles that reported results regarding technologies (hardware, software, or mobile apps) that were used to monitor or take care of the voice in occupational voice users were included. Results: After reviewing 4581 abstracts, 10 full text studies were included in the literature review. The technologies found include 30% hardware, 30% hardware plus software, and 50% mobile apps, with an overall TRL mean of 5.3 (SD ¼ 2.3). Conclusion: Further research is necessary for higher validity in the studies and to increase the readiness in the development of current technologies to offer more options for this population.